Teaching of research at the current university - Rodríguez de los Ríos, Luis (2018)
There is a paradigm shift in higher education with the shift from the information society to the knowledge society and the measurement of its performance globally. Priority is given to basic and technological research and inter- institutional and interdisciplinary collaboration. The University Law N ° 30220 assigns a decisive importance to him since stipulates a vice-rector of investigation. One of several ways to promote the research so located is through specific policies of implementation of teaching development for research from undergraduate to postdoctoral. Research is required for development and innovation and collaboration with companies for the training of job skills and entrepreneurship.